Early childhood care, education, and development in the Philippines principles, legal aspects, and public health implications - Estrada, Crystal Amiel M. (Philippine Journal of Health Research and Development, 2017)
The process of child development is unique in every child but the manner and sequence are predictable, hence early care and education must take into consideration the age of the child and the natural developmental stages of childhood. Early childhood care and education puts emphasis on the social, emotional, cognitive, and physical needs of the child for a strong foundation of learning and well-being all throughout life. Previous studies present evidence that early childhood education affects a child's holistic development into adulthood; therefore, addressing discrepancies between the existing care and education programs and children;s level of understanding is important to maximize a child's developmental potential. This review focused on early care and education in the Philippines and is public health implications. First, this review briefly discussed the basic principles and theories of child development and the legal and administrative fundamentals of early childhood care and development in the Philippines. It also provided a discussion on the public health implications of early child care and education. Finally, it concluded with providing recommendations ta parents and the education and health sectors which can contribute to the enhancement of early education in the Philippines.